Analisis Gambaran Pelaksanaan Sensus Harian Rawat Inap di Rumah Sakit - Pomarida Simbolon; Nagoklan Simbolon; Agnes Louise Lasmaida (Yayasan Literasi Sains Indonesia, 2025)
Daily inpatient census is a collection of patient data entering and leaving the ward. The purpose of the study was to determine the implementation of daily inpatient census in several hospitals. The implementation of the study was through literature studies by conducting descriptive analysis by describing the existing facts, then analyzing them, looking for similarities, views, and summaries of several studies. The results of this study showed that most of the implementation of the daily census still experienced many inconsistencies with SOP, delays and only a small part of the implementation of the daily census was in accordance with the SOP. The delay in returning the census was caused by the lack of awareness of human resources regarding the importance of the data that had been collected for the benefit of the hospital. SOP have not been implemented optimally, the supporting facilities and infrastructure for census activities are inadequate. In addition, there is a lack of leadership supervision of the implementation of census data filling activities. This will have an impact on the information that will be issued by the hospital regarding the health service activities that have been provided to patients. And besides that, the data that will be reported to various parties who need the data becomes inaccurate.